(3JMaI GdEfSGf aj GdYbGFO hGdCOjGfs - (3eMeO GdJejejs
(3ChdgG (B:s
(3CeG HYO abO cfJ GfJbjJ ef cJH TJi LedI TPQGJ eHGMK GdOjGfGJ ChQOJgG ai cJGHi CMSf GdbUU ai GdCfHGA hGdbUU Ke QCjJ Cf CdNUgG hCLeYgG ai QSGdI efaQOI aLeYJgG hSejJgG JMaI GdEfSGf s
(3BNQgG (B:s
(3jhVM HgG SHH Ch CSHGH WHjYjI eLghd GdMGOK ef GdMhGOK GfJgi s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3Yde GdcdGe (B_ (3JjehQ (B526) s
Keywords: (3GdJhMjO hGdedd hGdfMds